Wind of change? Cultural determinants of maternal labor supply - Barbara Boelmann; Anna Raute; Uta Schönberg (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
We investigate the role of cultural norms in shaping women's labor supply decisions after childbirth. Specifically, we are interested in the interplay between childhood socialization and adulthood environment. To that end, we leverage the setting of the German reunification when East Germany's gender egalitarian culture induced by socialism and West Germany's more traditional culture were brought together. We find that East German gender norms are persistent whereas West German ones are not. West German mothers adjust their behavior to that of their East German peers not only when immersed in East German environment but even after returning to the West.
Keywords: J1; J2; Z1; 330; gender gaps; cultural persistence; cultural adoption; maternal labor force participation; German reunification